The Hero that Kills his Writer - Abdelhakem, Slimane (Milev Journal of Research and Studies, 2022)
This paper initiates with stating the causes of the phenomenon of suicide. Unlike in Semitic religions, in America tends to be regarded as a psychological or sociological phenomenon. However, some suicidologists have asserted that the mere act of suicide provides sources of pleasure and therefore of motivation. Examples of atypical suicide are stated through ‘the largest suicide in a community’. Then the position of literature towards suicide .Then, International novels about the suicide of the heroes.such as Anna Karenina, Mrs. Dalloway, Veronica decides to die, Beware of pity. After that, the paper states some of famous writers and their suicide such as Kurt Vonnegut, Jack London, Hunter S. Thompson, Sylvia Plath, Raymond Chandler, David Foster Wallace. The bulk of this article ink has been shed on the’ The Hero that kills his writer’ taking Ernest Hemingway as a vivid example. Avoiding the temptation to fill up the paper with theoretical arguments on the various causes of the suicide of a person, even with the presence of common factors, the aim of the paper is to initiate a debate on the concerns regarding the death of literature writers and their characters. Examples of some prominent writers who committed suicide and how death haunted them in whatever they wrote. The conclusion shows the author’s point of view towards the suicide of the writers and opens a window to a further debate by asking rhetorical questions.